Antinociception induced by stimulating amygdaloid nuclei in rats: changes produced by systemically administered antagonists - Oliveira,M.A. (1998)
The antinociceptive effects of stimulating the medial (ME) and central (CE) nuclei of the amygdala in rats were evaluated by the changes in the latency for the tail withdrawal reflex to noxious heating of the skin. A 30-s period of sine-wave stimulation of the ME or CE produced a significant and short increase in the duration of tail flick latency. A 15-s period of stimulation was ineffective. Repeated stimulation of these nuclei at 48-h intervals produced progressively smaller effects. The antinociception evoked from the ME was significantly reduced by the previous systemic administration of naloxone, methysergide, atropine, phenoxybenzamine, and propranolol, but not by mecamylamine, all given at the dose of 1.0 mg/kg. Previous systemic administration of naloxone, atropine, and propranolol, but not methysergide, phenoxybenzamine, or mecamylamine, was effective against the effects of stimulating the CE. We conclude that the antinociceptive effects of stimulating the ME involve at least opioid, serotonergic, adrenergic, and muscarinic cholinergic descending mechanisms. The effects of stimulating the CE involve at least opioid, ß-adrenergic, and muscarinic cholinergic descending mechanisms.